PUBLIC ASSESSMENT OF THE PERFORMANCE DPRD’s TANGERANG CITY IN THE PANDEMIC PERIOD OF 2020 - William Yani WA; Deddi Fasmadhy Satiadharmanto; Retnowati WD Tuti (International Journal of Social Science, 2021)
The one-year performance of The DPRD's Tangerang City for the 2019-2020 period is Influenced by the Covid-19 Pandemic. The analysis of the performance of The DPRD's Tangerang City is not only seen from the three functions of legislative members such as Legislation, Budget, and Supervision, but also during the Covid-19 Pandemic, performance is seen from the role of The DPRD's Tangerang City in dealing with this Pandemic and the adaptation of new values ​​with technology compared to direct communication. This study was conducted with the aim of understanding and describing the performance of The DPRD's Tangerang City during the 2020 Covid-19 Pandemic and to find out and analyze the efforts made by The DPRD's Tangerang City members in dealing with the 2020 Covid-19 Pandemic. The method used in this research is a qualitative approach, the data collection is done based on interviews and literature study. This study in the finding that the performance of The DPRD's Tangerang City has declined in terms of quality and quantity due to the adapting situation during the Covid-19 Pandemic, but The DPRD's Tangerang City has shown a quick response in dealing with the Covid- 19 Pandemic and shows high concern for the condition of the community.